Etiology, Diagnosis, Clinic and Treatment of Cutaneous Leishmaniasis - Sultanov Akram Abdukholikovich; Khaitov Kakhramon Najmitdinovich; Togaev Akhror Turakulovich; Abdullaev Farrukh Abdullaevich (Genius Journals, 2022)
Cutaneous leishmaniasis can present with localized, chronic, recurrent, diffuse, and sharp forms. For diagnostics, dermatoscopy, microscopy of biopsy material, smears - prints, skin scrapings; inoculation on NNN medium, PCR, serological diagnostics. 4 types of histological manifestations of infection are characteristic: I - abundant amastigotes, II - macrophages, polymorphonuclear neutrophils, plasma cells, necrosis, III – early granuloma with focal accumulation of epithelial cells, lymphocytes and a small number of plasma cells, IV - well-formed epithelioid granuloma in the dermis with Langerhans giant cells, lymphocytes and epithelioid cells. First line drugs for cutaneous leishmaniasis are preparations of pentavalent antimony: sodium stibogluconate intravenously or intramuscularly, meglumine antimonate intravenously or intramuscularly, miltefosine orally
Keywords: cutaneous leishmaniasis; sodium stibogluconate; paromomycin; azoles